1995
DOI: 10.1111/j.1365-2222.1995.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum IgE in alcohol abusers

Abstract: Chronic alcoholism should be considered as a cause of increased total serum IgE, regardless of the severity of the underlying liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
65
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 30 publications
11
65
0
1
Order By: Relevance
“…Alcohol consumption is consistently associated with increased levels of serum total IgE in selected samples of alcohol abusers [17,19] in the general population [18,20] and in allergy clinics [21], as is evident in the present study. Previous reports showed that heavy drinking is associated with CCD sensitization [6,7,22,23].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Alcohol consumption is consistently associated with increased levels of serum total IgE in selected samples of alcohol abusers [17,19] in the general population [18,20] and in allergy clinics [21], as is evident in the present study. Previous reports showed that heavy drinking is associated with CCD sensitization [6,7,22,23].…”
Section: Discussionsupporting
confidence: 57%
“…From the initial CCD description in 1984 [16], Hymenoptera stings have been suspected as a source of CCD sensitization [15]. Additional factors for sensitization may include alcohol consumption, which increases total IgE levels [17,18,19,20,21] and is consistently associated with CCD sensitization [6,7,22,23]. This study aimed to investigate the prevalence of IgE-mediated CCD sensitization in patients who attended an allergy clinic due to suspicion of respiratory allergy.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2, alcohol consumption was a major factor causing increased IgE production in chronic pancreatitis patients [21][22][23]. This particular subgroup of patients showed serum IgE levels four times higher than those in control patients who consumed alcohol.…”
Section: Discussionmentioning
confidence: 81%
“…Serum IgE levels are commonly increased in patients with alcoholic cirrhosis, but not in cases of liver cirrhosis of a different origin [2, 3]. Serum IgE increase in alcoholics is unrelated to the severity of liver dysfunction [2, 34, 35, 36]. Moreover, low IgE levels have been observed in primary biliary cirrhosis [3].…”
Section: Discussionmentioning
confidence: 99%